Perioperative intravenous tranexamic acid reduces blood transfusion in primary cementless total hip arthroplasty - Sandri, Andrea; Mimor, Bogdan Florentin; Ditta, Alessandro; Finocchio, Eliana; Danzi, Vinicio; Piccoli, Pierluigi; Regis, Dario; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Blood loss and transfusion requirements are common in total hip arthroplasty. Tranexamic acid is one of the most interesting options to reduce the need for blood transfusions in a variety of surgical settings. The aim of this study was to assess the efficacy of perioperative intravenous traxexamic acid regarding blood transfusion rate and volume of transfused blood without increasing adverse events after primary elective cementless total hip arthroplasty. Methods: A comparative retrospective study was conducted in 86 healthy patients who had undergone primary cementless total hip artrhoplasty for severe joint diseases at a single institution. All surgical procedures were performed through an anterolateral Watson- Jones approach with the patient in supine position. Forty patients (TXA group) received tranexamic acid 1g as an intravenous bolus 10 minutes before skin incision and a further 1 g, diluted in 250 mL of saline solution, in continuous perfusion at 30 mL/h, following commencement of the surgery. Forty-six patients (control group) did not receive TXA. Outcome measures included BT rate, volume of transfused blood, deep vein thrombosis and occurrence of pulmonary embolism. Results: BT rate was significantly less for the TXA group (37.5%) compared with the control group (65%; p=0.011). The mean blood volume transfused was also significantly less for the TXA group (240 mL) compared with the control group (450mL; p=0.009). No adverse events occurred in any group. Conclusons: Perioperative intravenous tranexamic acid is effective in reducing blood transfusion rate and volume of transfused blood, without increasing the risk of thromboembolic events in patients undergoing primary cementless total hip arthroplasty.